Diplomado de Recipientes a Presión: Diseño de Recipientes a Presión conforme a la Sección VIII, Div.1 del Código ASME - Rivera Mendoza, Orlando (My University, 2005)
Welded Joints Two terms apply to welded joints in the code. One of these descriptions is joint category. Category defines the location of a join within the vessel. For example, a category a joint would be a long seam or a seam that would see the same stresses as a long seam.
Keywords: Diseño de recipientes a presión; Types of service, design loadings, welded joints, major changes to UW-11 and UW-12, radiography, vessels, corrosion allowance, circumferential stress, shells made from pipe UG-31, stresses, UG-16 (b), type of head designs, UG-32 (j), UG-32 (b), braced and stayed surfaces UG-47, unstayed flat heads and covers UG-34